Optimalisasi Produktivitas Alat Berat Galian Dan Timbunan Konstruksi Perumahan Balikpapan - Kahandanie, Ferdy; Kartika, Desak Made Ristia (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Galian dan Timbunan work is a crucial step in the construction of a project, and its efficiency greatly affects the productivity of the equipment. The purpose of this study is to analyze the productivity of the cutting and filling equipment in the Mentari housing, Balikpapan, construction project, which has complex lahan characteristics. The research methodology that is used is a quantitative deskriptif. Data collection is done through lapangan observation to record the duration of the equipment and document analysis related to the project's timeline. Data is analyzed to determine the productivity of each of the following equipment: the Kobelco SK200-10 excavator, the United Tractors 20 m³ and Hino Dutro 7 m³ dump trucks, the bulldozer D85E-SS, and the Sany SSR120-C10 vibration roller. The study's findings indicate that the productivity of an excavator was 103,845 m³/hours over 22 day, while that of a United Tractors dump truck was 96,851 m³/ hours over 20 Day The Hino Dutro dump truck weighs 32,740 m³/hours for 10 Day, the bulldozer weighs 282,05 m³/hours for 1 Day, and the vibration roller weighs 158,82 m³/ hours for 1 Day. This study provides important information for project planning, especially when choosing appropriate tools and estimating work duration.